Prenatal stress alters diazepam withdrawal syndrome and 5HT1A receptor expression in the raphe nuclei of adult rats. (25th August 2016) - Lakehayli, S.; Said, N.; El Khachibi, M.; El Ouahli, M.; Nadifi, S.; Hakkou, F.; Tazi, A.
Highlights: Maternal exposure to chronic stress has long-lasting effects on the serotoninergic system. Prenatal stress down-regulates 5HT1A receptor expression in the raphe nuclei of adult offspring. Repeated adult diazepam exposure increases 5-HT1A mRNA expression in control rats. Prenatal stress prevents the diazepam-induced increase in 5-HT1A mRNA expression in adult rats. Abstract: Early-life events have long-term effects on brain structures and cause behavioral alterations that persist into adulthood. The present experiments were designed to investigate the effects of prenatal stress on diazepam-induced withdrawal syndrome and serotonin-1A (5HT1A) receptor expression in the raphe nuclei of adult offspring. The results of the present study reveal that maternal exposure to chronic footshock stress increased the anxiety-like behavior in the prenatally stressed (PS) animals withdrawn from chronic diazepam (2.5 mg/kg/day i.p for 1 week). Moreover, prenatal stress induced a down-regulation of 5HT1A mRNA in the raphe nuclei of adult offspring. To our knowledge, this study is the first to demonstrate that maternal exposure to chronic footshock stress enhances diazepam withdrawal symptoms and alters 5HT1A receptor gene expression in the raphe nuclei of adult offspring. Thus, more studies are needed to clarify the mechanisms underlying the decrease of 5HT1A receptors expression in the raphe nuclei of PS rats.